PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO KELONTONG SINAR MAJU DI KABUPATEN BONE - A. Ainin Amelia; Andi Mappatompo; Basri Basir MR (STKIP Subang, 2026)
This study aims to determine and analyze the effect of product quality and service on customer satisfaction at Sinar Maju Grocery Store in Bone Regency. The research applies a quantitative approach using an associative method. Data were collected through questionnaires distributed to customers of Sinar Maju Grocery Store as respondents. The data analysis techniques used include validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of statistical software. The results indicate that product quality has a positive and significant effect on customer satisfaction. Service also has a positive and significant effect on customer satisfaction. These findings imply that the better the product quality and service provided, the higher the level of customer satisfaction. Therefore, the store needs to maintain and improve product quality and service in order to create customer loyalty amid increasingly competitive business conditions.